2017
DOI: 10.1002/ajcp.12209
|View full text |Cite
|
Sign up to set email alerts
|

Natural Mentors, Social Class, and College Success

Abstract: Natural mentors provide advice, moral support, and assistance to adolescents who aspire to obtain a postsecondary degree, but past studies of the benefits of having an informal adult mentor have yet to resolve several issues. Our analyses of a national sample of high school graduates test three hypotheses: (H1) natural mentoring increases the odds of college attendance and completion, (H2) guidance and career advice are more important for college success than encouragement or role modeling, and (H3) students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In particular, studies using Add Health, a large, nationally representative dataset, have found that youth from marginalized backgrounds experience stronger benefits of mentoring compared to their more privileged peers, and that mentors based in schools (i.e., teachers) and/or with high educational capital have the strongest impact on academic outcomes. For example, Reynolds and Parrish () recently found that having a natural mentor promoted college attendance only among poor and working‐class youth; mentoring did not impact college attendance for middle‐ and upper‐class youth. Examining mentors’ social roles and statuses, Add Health studies have also found that youth with mentors outside of their families were more likely to graduate high school, attend college, and complete college degrees compared to both unmentored youth and those with familial mentors (Dubois & Silverthorn, ).…”
Section: Outcomes and Processes Of Natural Mentoringmentioning
confidence: 99%
“…In particular, studies using Add Health, a large, nationally representative dataset, have found that youth from marginalized backgrounds experience stronger benefits of mentoring compared to their more privileged peers, and that mentors based in schools (i.e., teachers) and/or with high educational capital have the strongest impact on academic outcomes. For example, Reynolds and Parrish () recently found that having a natural mentor promoted college attendance only among poor and working‐class youth; mentoring did not impact college attendance for middle‐ and upper‐class youth. Examining mentors’ social roles and statuses, Add Health studies have also found that youth with mentors outside of their families were more likely to graduate high school, attend college, and complete college degrees compared to both unmentored youth and those with familial mentors (Dubois & Silverthorn, ).…”
Section: Outcomes and Processes Of Natural Mentoringmentioning
confidence: 99%
“…Previous research has found that informal mentoring is associated with many of such building blocks. For example, mentored youth are more likely to feel connected to their school (Black et al, 2010), have better grades (Chang et al, 2010), attend college (DuBois & Silverthorn, 2005; Reynolds & Parrish, 2018) or receive a bachelor’s degree (Erickson et al, 2009; Fruiht & Chen, 2018; Miranda-Chan et al, 2016). Those who have a mentor in adolescence are more likely to be employed in young adulthood (DuBois & Silverthorn, 2005), have a bank account or own a car (Greeson et al, 2010), and to have higher incomes (Hagler & Rhodes, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to clarify that there are different styles of mentors in academia, each characterized by aspects of the personality of the individual who serves as mentor. The following are the most popular types of academic mentors: [35]. This style of mentor is considered a specialist in his/her field, grants opportunities for the learning of others, provides opportunities for mentees to practice new skills.…”
Section: Type Of Academic Mentorsmentioning
confidence: 99%